Mastering marketing agility transform your marketing teams and evolve your organization - Fryrear, Andrea (Berrett-Koehler Publishers, 2020)
The leading authority on agile marketing shows how to build marketing operations that can pivot freely and yet remain committed to priorities. /> />As a marketer, are you tired of chasing marketing fads and algorithm rumors that seem to change every couple of months' This guide to building the perfect marketing department will help you achieve the latest and greatest without having to rebuild your operations from scratch every time the wind shifts. Agile strategies have been the accepted modus operandi for software development for two decades, and marketing is poised to follow in its footsteps. As the audiences we market to become ever more digital, agile frameworks are emerging as the best and only way to manage marketing. This book is a signpost showing the way toward the agile future of marketing operations, explaining how every role, from social media intern up to chief marketing officer, can work in unison, responding to the market's demanding challenges without losing focus on the big picture. /> />You will learn what it takes for marketing agility to thrive'customer focus, transparency, continuous improvement, adaptability, trust, bias for action, and courage'along with the antipatterns that can drag you down. Most important, you will learn how to implement the systems, strategies, and practices that will truly transform your marketing operations. />